PEMBINAAN NARAPIDANA NARKOTIKA DAN OBAT OBATAN BERBAHAYA (NARKOBA) DALAM PERSPEKTIF KEHIDUPAN RELIGIUSITAS - Teguh Suratman (University of Merdeka Malang, 2016)
Research on narcotic drug guidelines and dangerous drugs (narcotics) in the perspective of religious life, carried away came out with the result that prisoners in juridical are referred to as those under drug jurisdiction since early caught law enforcement officers and, caught, for allegedly committing drug crimes, behave crimes, against the law, and committing their acts contrary to prevailing norms. The perpetrators under drug jurisdictionDealers in prisons on average have high intelligence, often acts that do not escape even though the officer was caught. In this case, the penitentiary as the final institutionThe sequence in the law enforcement process and the care of illegal drug traffickers, to explore, change their Mindcrime becomes a religious behavior in his life. Attitudes, actions, and the character of drugs are good and well behavedReligious people begin to be submitted to members, parole, and rejected by society views the importance of religious or dependable appreciation as the basis for everyday behavior it has had and is used by illicit drugs, therefore religion is adopted and the course is simple in jargon called the id of Islam card. It lives within its limitations in motion, facility, relationship with the other side, attached to a discipline of strict rules, especially while in a cell prison. But, still with shelter reverted back